Development of laser cutting and engraving machine utilising PC-NC controller - Nik Mohamed, Nik Mohd Zuki; Noor, M. M.; Rose, Ahmad Nasser Mohd; Razali, Noraini Mohd; Daud, Rosdi; Shalahim, N. S M; Ahmad, Syarifah Nur Aqida Syed (2008)
Laser machining is one of the most popular applications of the laser material processing. New processes such as laser cutting and laser engraving have been evolved ever since laser machining became popular in the manufacturing industries over the past decades. Therefore, this study developed the laser cutting and engraving machine by utilizing PC-NC controller. The controlling system that has been developed is capable of executing a stored program correctly and moving the laser smoothly in the desired way. Hence, the PC-NC controller specifically tailored for laser cutting and engraving which can control all the relevant parameters in real time except the laser beam power. So the moving table which attached to the laser head can run smoothly and control the crucial parameters accurately. The laser machine then is tested with different types of work piece to investigate the effectiveness of cutting and engraving processes using this system. In general, the laser system for cutting and engraving utilizing PC-NC controller successfully developed.